The role of regional conflict in destabilizing Iraqi national security; An analytical geopolitical study. - ABDULKADHIM OBAID, BUSHRA (International Journal of Psychosocial Rehabilitation, 2020)
The present study deals with local and regional variables affecting the security and stability of the Iraqi state. It identifies challenges and threats of national security. Relations among the influencing countries are highlighted. The US invasion in 2003 allowed regional countries to interfere in the internal and external affairs of Iraq as it is of great importance for these countries; Iran, Turkey, and the United States of America due to its geostrategic importance in the regional political scene and richness with natural resources such as oil and gas. Regional conflict imposed severe pressures on the political and security situation in Iraq, especially in cases of difference and contradiction of Interests between those parties. That was among many reasons that contributed to the destabilization of the Iraqi political situation because of quotas, sectarianism, disregard of national cohesion, and the absence of effective leadership that is capable of drawing features of preserving its sovereignty and enhancing opportunities of circumventing a single national identity. Therefore, The regional system in general should be reformulated regarding the new conditions imposed by the geostrategic conditions in the region, which have become a major challenge for the Arab region, its political future, and its existence.